1992
DOI: 10.1159/000186813
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Latent Heart Failure by Mild Hypocalcemia after Parathyroidectomy in a Long-Term Hemodialysis Patient

Abstract: A 60-year-old uremic patient treated with hemodialysis for 13 years developed acute hypotension during hemodialysis and overt heart failure subsequently in a period of relatively mild hypocalcemia after parathyroidectomy. Blood pressure during hemodialysis was maintained by continuous calcium infusion alone. Cardiomegaly was improved by normalization of serum calcium. The cardiac complication is considered to be exacerbation of the underlying myocardial dysfunction by the acute decline of serum calcium which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…This study found that 3 months after normalization of calcium by oral therapy, both maximum cardiac output and maximum heart rate demonstrated a statistically significant increase during peak exercise, thus concluding that hypocalcaemia impairs cardiac performance, but that this impairment is reversible with calcium replacement [5] . Several case reports have demonstrated similar findings; that is, hypocalcaemia is a reversible and, more importantly, easily treatable cause of heart failure [610] .…”
Section: Discussionmentioning
confidence: 73%
“…This study found that 3 months after normalization of calcium by oral therapy, both maximum cardiac output and maximum heart rate demonstrated a statistically significant increase during peak exercise, thus concluding that hypocalcaemia impairs cardiac performance, but that this impairment is reversible with calcium replacement [5] . Several case reports have demonstrated similar findings; that is, hypocalcaemia is a reversible and, more importantly, easily treatable cause of heart failure [610] .…”
Section: Discussionmentioning
confidence: 73%
“…Consequently, the clinical features of hungry bone syndrome are due to hypocalcemia, hypophosphatemia, hypomagnesemia, and hyperkalemia.The serum calcium typically reaches a nadir two to four days postoperatively [2]. Hypocalcemia resulting in overt heart failure has been described in patients with latent myocardial dysfunction where cardiomegaly and pulmonary congestion resolved after normalization of the serum calcium [9,10]. Careful monitoring two to four times per day for the first few postoperative days is required to prevent and treat symptomatic hypocalcemia, which can be potentially catastrophic.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying hyperparathyroidism can either be primary or secondary due to endstage renal disease. Acute hypocalcemia has been known to cause myocardial dysfunction, poor myocardial performance and even congestive heart failure either with or without hypotension [3][4][5][6][7][8]. We herein present a woman with profound hypocalcemia due to hbswho progressed to cardiopulmonary arrest.…”
Section: Introductionmentioning
confidence: 96%
“…This occurs as a consequence of low circulating parathyroid hormone resulting in decreased osteoclast mediated bone resorption . When hypocalcaemia is severe, life‐threatening complications can occur including seizure, arrhythmia and decompensated heart failure …”
Section: Introductionmentioning
confidence: 99%
“…4,5 When hypocalcaemia is severe, life-threatening complications can occur including seizure, arrhythmia and decompensated heart failure. 6,7 Recent studies into HBS suggest an incidence of 27%-31% in the ESKD population. [8][9][10] Despite the high incidence, there are conflicting data regarding its clinical course, risk factors and the best strategy for its prevention.…”
Section: Introductionmentioning
confidence: 99%